Allylic Hydroxylation Activity Is a Source of Saponin Chemodiversity in the Genus Glycyrrhiza - Fanani, Much Z. (2021)
Licorice (Glycyrrhiza) produces glycyrrhizin, a valuable triterpenoid saponin, which exhibits persistent sweetness and broad pharmacological activities. In the genus Glycyrrhiza, three species, Glycyrrhiza uralensis, Glycyrrhiza glabra and Glycyrrhiza inflata, produce glycyrrhizin as their main triterpenoid saponin, which has a ketone group at C-11. Other Glycyrrhiza species produce mainly oleanane-type saponins, which harbor homoannular or heteroannular diene structures that lack the C-11 ketone. Although the glycyrrhizin biosynthetic pathway has been fully elucidated, the pathway involving saponins with diene structures remains unclear. CYP88D6 from G. uralensis is a key enzyme in glycyrrhizin biosynthesis, catalyzing the sequential two-step oxidation of β-amyrin at position C-11 to produce 11-oxo-β-amyrin. In this study, we evaluated the functions of CYP88D6 homologs from the glycyrrhizin-producing species G. glabra and G. inflata and from the non-glycyrrhizin-producing species Glycyrrhiza pallidiflora and Glycyrrhiza macedonica, using yeast engineered to supply β-amyrin as a substrate. Yeast expressing CYP88D6 homologs from glycyrrhizin-producing species produced 11-oxo-β-amyrin. However, yeast expressing CYP88D6 homologs (such as CYP88D15) from the non-glycyrrhizin-producing Glycyrrhiza species accumulated oleana-9(11),12-dien-3β-ol and oleana-11,13(18)-dien-3β-ol; these diene compounds are non-enzymatic or yeast endogenous enzymatic dehydration derivatives of 11α-hydroxy-β-amyrin, a direct reaction product of CYP88D15. These results suggest that the activities of CYP88D6 homologs, particularly their ability to catalyze the second oxidation, could influence glycyrrhizin productivity and diversify the chemical structures of saponins in Glycyrrhiza plants. A synthetic biological approach to engineer CYP88D15 could enable the production of pharmacologically active saponins with diene structures, such as saikosaponins, whose biosynthetic pathways have yet to be fully characterized.